Biodex© training post-stroke for postural stability in the upper trunk: A pilot study - Helena W. Nel; Witness Mudzi; Elizabeth C. Janse van Vuuren; Eustasius Musenge (South African Journal of Physiotherapy, 2020)
Background: Stroke affects upper trunk postural stability and upper limb function in approximately 85% of stroke survivors. Upper trunk postural stability is essential for functioning of the upper limb and is a prerequisite for hand function. The rehabilitation of the upper limb and upper trunk post-stroke remains a challenge because of poor recovery of motor and sensory function.